Dual-Task Performance in GBA Parkinson’s Disease - Karin Srulijes; Kathrin Brockmann; Senait Ogbamicael; Markus A. Hobert; Ann-Kathrin Hauser; Claudia Schulte; Jasmin Fritzen; Michael Schwenk; Thomas Gasser; Daniela Berg; Walter Maetzler (Parkinson's Disease)
Introduction. Parkinson’s disease patients carrying a heterozygous mutation in the gene glucocerebrosidase (GBA-PD) show faster motor and cognitive decline than idiopathic Parkinson’s disease (iPD) patients, but the mechanisms behind this observation are not well understood. Successful dual tasking (DT) requires a smooth integration of motor and nonmotor operations. This study compared the DT performances between GBA-PD and iPD patients. Methods. Eleven GBA-PD patients (p.N370S, p.L444P) and eleven matched iPD patients were included. Clinical characterization included a motor score (Unified PD Rating Scale-III, UPDRS-III) and nonmotor scores (Montreal Cognitive Assessment, MoCA, and Beck’s Depression Inventory). Quantitative gait analysis during the single-task (ST) and DT assessments was performed using a wearable sensor unit. These parameters corrected for UPDRS and MoCA were then compared between the groups. Results. Under the DT condition “walking while checking boxes,” GBA-PD patients showed slower gait and box-checking speeds than iPD patients. GBA-PD and iPD patients did not show significant differences regarding dual-task costs. Conclusion. This pilot study suggests that DT performance with a secondary motor task is worse in GBA-PD than in iPD patients. This finding may be associated with the known enhanced motor and cognitive deficits in GBA-PD compared to iPD and should motivate further studies.